2022
DOI: 10.1093/cvr/cvac118
|View full text |Cite
|
Sign up to set email alerts
|

Molecular stratification of arrhythmogenic mechanisms in the Andersen Tawil syndrome

Abstract: Andersen Tawil Syndrome (ATS) is a rare inheritable disease associated with loss-of-function mutations in KCNJ2, the gene coding the strong inward rectifier potassium channel Kir2.1, which forms an essential membrane protein controlling cardiac excitability. ATS is usually marked by a triad of periodic paralysis, life-threatening cardiac arrhythmias and dysmorphic features, but its expression is variable and not all patients with a phenotype linked to ATS have a known genetic alteration. The mechanisms underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…This might be due to sodium inward current (I Na ) modification induced by the Kir2.1 E299V mutation. 21 , 34 In an additional group of experiments, we measured I Na in atrial and ventricular cardiomyocytes. In Figure 7 A superimposed IV relations (Ai), and activation and inactivation curves (Aii) from Kir2.1 WT and Kir2.1 E299V atrial cardiomyocytes showed that the mutation did not modify either I Na density or its biophysical properties (Aiii and Aiv).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to sodium inward current (I Na ) modification induced by the Kir2.1 E299V mutation. 21 , 34 In an additional group of experiments, we measured I Na in atrial and ventricular cardiomyocytes. In Figure 7 A superimposed IV relations (Ai), and activation and inactivation curves (Aii) from Kir2.1 WT and Kir2.1 E299V atrial cardiomyocytes showed that the mutation did not modify either I Na density or its biophysical properties (Aiii and Aiv).…”
Section: Resultsmentioning
confidence: 99%
“… 20 Trafficking-deficient mutations in one of these channels reduce the surface expression and current density of the other. 21–25 However, it is unknown whether gain-of-function mutations in one or the other channel modify such interactions or result in unforeseen electrical remodelling mediated by changes in other interacting proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Defects in PIP 2 binding are a major pathophysiologic mechanism underlying the loss-of-function phenotype for several ATS1-associated mutations. 5,9–11…”
mentioning
confidence: 99%
“…1,2 Kir2.1 is ubiquitously expressed throughout the human body, and ATS1 mutations predispose patients to a triad of alterations including periodic paralysis, dysmorphias, and arrhythmias that can lead to sudden cardiac death 3,4 by mechanisms that remain unclear. 5 In the heart, Kir2.1 is responsible for the inward rectifier K + current (I K1 ), 6 which plays a central role in the maintenance of the resting membrane potential (RMP) and the final phase of action potential (AP) repolarization. 7 Therefore, loss-of-function mutations in Kir2.1 lead to a substantial decrease in I K1 , with consequent membrane depolarization at rest, as well as AP duration and corrected QT (QTc) interval prolongation.…”
mentioning
confidence: 99%
See 1 more Smart Citation